Female in football: An unbalanced world - Wilhelmsen, Linda (Septentrio Conference Series, 2019)
Purpose For centuries, men have dominated football organizations in all levels, and the imbalance in status between male and female football is unparalleled in the world of sports. This may affect female football by means of career opportunities, resource allocation and organizational performance. This study will explore managerial, organizational and cultural parameters that have an impact on women’s career possibilities in football organizations as players, coaches and leaders. The following research questions will be explored: In what way do governing mechanisms such as culture, attitudes and values have an impact on female positions in football organizations? How do organizational structures and cultures in football organizations affect women's career opportunities? How do power mechanisms, gender roles and stereotypes, unbalanced resource access, commercial investment impact female versus male football? Methodology Data will be collected among female football organizations in the two top football leagues in Norway. Qualitative data will be collected by interviews, field notes from facilitated face-to-face meetings with World Café dialogue technique and participant evaluations, whereas quantitative data will be collected by surveys and registry data. Implications Female football has received very little research attention, and as such, findings from the present project will provide novel insight regarding the impact of organizational performance for women’s opportunity for a career in football. Directing attention towards female participation in football organizations may increase participation and positions of trust within the organizations.